Rwandan Farmers’ Perceptions of the Acoustic Environment and the Potential for Acoustic Monitoring - Destiny Kwabla Amenyedzi; Micheline Kazeneza; Frederic Nzanywayingoma; Philibert Nsengiyumva; Peace Bamurigire; Emmanuel Ndashimye; Anthony Vodacek (Agriculture)
Monitoring the farm acoustic environment can provide important information about processes affecting crop production. This paper assesses farmers’ knowledge and attitudes toward acoustic technology for farm monitoring in Rwanda. Stratified random sampling was used to select 430 farmers from 3 sectors. Demographic, farm, and technical knowledge data were collected from farmers with a survey. Cross-tabulation results show farmers with secondary and university education are more interested in acoustic technology than those with a primary education and farmers engaged in commercial farming are more interested in technology for monitoring acoustic sources than subsistence farmers. However, nearly all farmers are willing to deploy a listening technology to monitor the acoustic environment. Farmers have a clear priority to listen to animals on the farm, whether they are pests (specifically, birds) or livestock. A chi-square test of independence indicates a significant relationship between farmers’ consideration of technology for farm monitoring and their attitudes toward sound monitoring. Farmers want a technological solution, but demand that the solution be low-cost and provide a simple alert. The results inform system requirements for an Internet of Things acoustic network that can deliver this information to the farmer.